Adolescent girls’ and young mothers’ knowledge and use of antenatal care in the Ahafo Region, Ghana: A cross-sectional study - Tabiri, Joseph; Adzordor, Patience; Bawontuo, Vitalis; Ziblim, Shamsu-Deen; Mchunu, Gugu G.; Pillay, Julian D.; Kuupiel, Desmond (African journal of primary health care & family medicine, 2024)
Antenatal care (ANC) is crucial to reducing maternal and neonatal deaths, but few studies examined adolescent girls' and young women's ANC utilisation and knowledge in Ghana. To assess adolescents' and young mothers' knowledge of ANC, utilisation and factors influencing its use in Ghana. Tano North Municipality, Ahafo Region. This community-based, cross-sectional study involved 440 adolescent and young mothers (between 10 and 24 years). A structured questionnaire was employed to collect data face-to-face. Descriptive and statistical analyses were performed, and p  0.05 was considered statistically significant. Of the 440 respondents, most were aged 20-24 years (61.2%), married (30.0%), Christians (78.2%), completed junior high school (JHS) (47.8%) and traders (38.9%). Postnatal mothers were 71.6% (315), and all had utilised ANC services. Antenatal care knowledge was good among 75% (330) respondents, with no significant variation by age. Religion influenced knowledge, with Muslims having lower knowledge. Antenatal care utilisation was high ( 50%) among those aged 15-19 years, married, Christians, JHS graduates and traders. Age, marital status and employment type significantly influenced ANC utilisation. Individuals in the age group 15-19 years and married women demonstrated higher odds of utilising ANC services. Casual workers and unemployed respondents were found to have lower odds of utilising ANC services compared to traders. Age, marital status, and employment type influenced ANC utilisation in the Ahafo Region. Adolescent mothers under 15 years had lower rates, requiring targeted interventions to improve pregnancy outcomes.Contribution: This study highlights the knowledge and factors influencing ANC use in Ahafo Region and adds to the existing research evidence on ANC.